2
$\begingroup$

Let $f:\mathbb{R}_+\rightarrow \mathbb{R}_+$ be a given monotonically increasing, continuous function. For example, consider $f(x) = x$.

How can I determine (if one exists) a monotonically increasing function $g:\mathbb{R}_+\rightarrow \mathbb{R}_+$ such that, for every $t\ge 0$,

  • $g(t) \le f(t)$ and
  • the area of $\{(x,y) : x \ge t, g(x) \le y \le f(t)\}$ equals $f(t)$?

The diagram below illustrates the area in question, labeled $A$, for a single $t$. It is the intersection of an axis-parallel rectangle (with upper-left corner $(t, f(t))$, and upper and left boundaries shown with dashed lines in the figure) and the area above the curve $\{(x, g(x)) : x \ge 0\}$.

enter image description here

I would accept an answer for just the special case when $f(x) = x$. In this case, surely $g(x) = f(x) - \Theta(\sqrt x)$ (for large $x$), but I'm looking for a more precise answer.

For the case when $f(x) = e^x$, the answer appears to be $g(x) = e^{x-c}$ for $c\approx 1.84$.

$\endgroup$
1
$\begingroup$

The question is interesting. Here are some developments. At the end of the answer, I found a closed-form expression for $g$ in the case $f(t)=t$.

Let us define the function $$ h(t) = g^{-1}(f(t)), $$ which defines the argument for which $g$ intersects with $f(t)$, see the figure below. (Just in case, $g^{-1}$ is the inverse of $g$. If $g$ is strictly monotone, then $g^{-1}$ truly exists. But the situation when $g$ has some "flat" parts is also ok, in fact.)

enter image description here

Let us denote the considered set as $A(t)$, i.e., $$ A(t) := \{(x,y): x \geq t,~ g(x) \leq y \leq f(t)\}, $$ and denote its area as $|A(t)|$. By the assumption, we require $|A(t)| = f(t)$ for each $t \geq 0$.

Let us explicitly calculate $|A(t)|$. We have $$ f(t) = |A(t)| = f(t)(h(t)-t) - \int_t^{h(t)} g(s) \, ds, $$ i.e. $|A(t)|$ is the area of the rectangle with sides $f(t)$ and $(h(t)-t)$, minus the area of the set which lies below $g$. Therefore, $$ \tag{1} \boxed{f(t)(h(t)-t-1) = \int_t^{h(t)} g(s) \, ds \quad \text{for all } t \geq 0.} $$

This equation already gives some information about $g$. Namely, we necessarily have $$ h(t) = g^{-1}(f(t)) \geq t+1, $$ which implies (by the monotonicity of $g$) that $$ f(t) \geq g(t+1). $$ In particular, $f(0) \geq g(1)$. For example, if $f(t)=t$, then $g(t)=0$ for all $t \in [0,1]$, and only for some $t >1$ it starts to grow.

A bit more developed bound can be obtained by estimating the integral on the right-hand side of (1) from below (by the monotonicity of $g$): $$ f(t)(h(t)-t-1) \geq g(t) (h(t)-t). $$ In particular, we see the following property:

If $f(0)>0$, then $f(0) > g(0)$. Or, equivalently, if $f(0)=g(0)$, then $f(0)=g(0)=0$.


Suppose now that $f$ and $h$ are differentiable. Since the equality (1) holds for all $t \geq 0$, we can differentiate both sides and obtain $$ f'(t)(h(t)-t-1) + f(t)(h'(t)-1) = g(h(t)) h'(t) - g(t). $$ Note that, by definition of $h$, we have $g(h(t))=f(t)$. That is, $$ \tag{2} \boxed{f'(t)(h(t)-t-1) - f(t) + g(t) = 0 \quad \text{for all } t \geq 0.} $$ More or less, this is the equation for $g$, under the assumption that $f$ and $h$ are differentiable. But it is not explicit, since it contains the inverse function $g^{-1}$. Note that $h$ can be nondifferentiable. Indeed, if we assume that (2) holds all the time, then if $f'(0)=0$, we have $f(0)=g(0)$. However, if, additionally, $f(0)>0$, then we get a contradiction from the property stated above. So, the nondifferentiability of $h$ occurs when $f'=0$.

However, I conjecture that if $f'(t)>0$ for all $t$, then (2) is valid. Suppose, this is true. Then, in the particular case $f(t)=t$, we get the following elegant equation for $g$: $$ g(t) + g^{-1}(t) = 2t+1, $$ which gives the recurrence formula $$ t = g(2t+1-g(t)). $$ It is possible to resolve it step by step. For instance, here are first few steps (see the figure below): $$ g(t) = \left\{ \begin{aligned} &0, &&t \in [0,1];\\ &\frac{t-1}{2}, &&t \in [1,3];\\ &\frac{2t-3}{3}, &&t \in [3,6];\\ &... \end{aligned} \right. $$ It can be seen that such $g$ is indeed what we need. That is, the application of (2) is ok.

enter image description here

$\endgroup$
  • $\begingroup$ Very nice. To continue your calculation, the closed form seems to be that $g(t) = t\, i\, / (i+1) - i/2$ for $i$ such that $$t\in \Big[{i+1 \choose 2}, {i+2 \choose 2}\Big].$$ $\endgroup$ – Neal Young May 10 '18 at 0:22
  • $\begingroup$ Yeah, it could to be something like that. Moreover, if we consider $f(t)=e^t$ and use the ansatz $g(t)=e^{t-c}$, then (2) shows that $c$ satisfies the following equations: $e^{-c}=2-c$. That is, $c=1.8414...$, as you wrote. $\endgroup$ – Voliar May 10 '18 at 8:50

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.